An Application of Statistical Methods of Indirect Estimation and Projection of Internal Migration Flows Within the Portuguese Mainland - Mendes, Maria Filomena (2013)
The study of migration flows is always problematic, essentially because there is not a systematic process of collecting background information. In the case of internal migration, restrictions on the available data are even more problematic and make it totally unfeasible to measure directly those movements. When the data on (regional) migration is incomplete, inadequate, or unavailable, the estimation or quantification of regional migration flows is made possible by the application of indirect methods of estimation. Andrei Rogers, along with several others, developed and tested over several years methodologies that allow us to analyze and quantify indirectly the different behaviors of regional migration. These methodologies are applied in the chapter, considering the case of Portugal.